The Influence of Online Customer Reviews, Brand Trust, and Perceived Value on Purchase Decisions of Daviena Skincare on TikTok in Surabaya - Arifin, Annisa Putri; Aminah, Siti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study was conducted to analyze the extent of the influence of Online Customer Reviews, Brand Trust, and Perceived Value on the Purchase Decision of Daviena Skincare on TikTok in Surabaya City. A quantitative methodology was applied in this study using a questionnaire as the survey instrument, distributed to 112 respondents selected through purposive sampling. The analysis method used was Partial Least Square based on Structural Equation Modeling (PLS-SEM), which was run using the SmartPLS4 application to obtain model estimation results. The study found that Online Customer Reviews did not have a significant effect on Purchase Decisions. Meanwhile, Brand Trust and Perceived Value were found to have a positive and significant effect on Purchase Decisions. These findings indicate that although online reviews are widely available on TikTok, factors such as brand trust and consumers' perceptions of product value remain the primary determinants in purchase decision-making. Based on these findings, it is hoped that Daviena Skincare can continue to build and maintain consumer trust and enhance product value perceptions through consistent quality, transparent information, and good service, in order to retain and increase customer loyalty.